Dietary Fats, Human Nutrition and the Environment: Balance and Sustainability - Meijaard, Erik; Abrams, Jesse F.; Slavin, Joanne L.; Sheil, Douglas (Frontiers in Nutrition, 2022)
Dietary fats are essential ingredients of a healthy diet. Their production, however, impacts the environment and its capacity to sustain us. Growing knowledge across multiple disciplines improves our understanding of links between food, health and sustainability, but increases apparent complexity. Whereas past dietary guidelines regarding, for example, saturated fats and cholesterol, sought to minimize consumption, recent studies indicate more complex links with health. Guidelines differ between regions of general poverty and malnutrition and those where obesity is a growing problem. Optimization of production to benefit health and environmental outcomes is hindered by limited data and shared societal goals. We lack a detailed overview of where fats are being produced, and their environmental impacts. Furthermore, the yields of different crops, for producing oils or feeding animals, and the associated land needs for meeting oil demands, differ greatly. To illuminate these matters, we review current discourse about the nutritional aspects of edible fats, summarize the inferred environmental implications of their production and identify knowledge gaps.